2020
DOI: 10.1186/s12957-020-01910-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between pylorus-preserving and distal gastrectomy in surgical safety and functional benefit with gastric cancer: a systematic review and meta-analysis

Abstract: Background: Due to better functional outcomes, pylorus-preserving gastrectomy (PPG) has been widely applied for early gastric cancer (EGC) patients as an alternative to distal gastrectomy (DG). However, controversies still persist regarding the surgical efficacy and oncological safety of PPG. Methods: Original studies comparing PPG and DG for EGC were searched in PubMed, Embase, and the Cochrane Register of Controlled Trials up to December 2019. The weight mean difference, standardized mean difference, or odds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…PPG has several advantages over DG for patients with EGC in the middle third of the stomach, including surgical outcomes and long-term nutritional status [ 27 , 39 , 40 , 51 , 54 , 55 ]. A meta-analysis of 4871 patients in one randomized clinical trial (RCT) and 20 non-RCTs showed that PPG was potentially superior to DG in terms of lower incidence of anastomotic leakage, dumping syndrome, gastritis, and bile reflux, and better recovery of total protein, albumin, hemoglobin, and weight [ 55 ]. As shown in Table 2 , the changes in body weight following PPG and DG were 93.1–97.0% and 90.0–95.0%, respectively.…”
Section: Pylorus-preserving Gastrectomy (Ppg)mentioning
confidence: 99%
See 1 more Smart Citation
“…PPG has several advantages over DG for patients with EGC in the middle third of the stomach, including surgical outcomes and long-term nutritional status [ 27 , 39 , 40 , 51 , 54 , 55 ]. A meta-analysis of 4871 patients in one randomized clinical trial (RCT) and 20 non-RCTs showed that PPG was potentially superior to DG in terms of lower incidence of anastomotic leakage, dumping syndrome, gastritis, and bile reflux, and better recovery of total protein, albumin, hemoglobin, and weight [ 55 ]. As shown in Table 2 , the changes in body weight following PPG and DG were 93.1–97.0% and 90.0–95.0%, respectively.…”
Section: Pylorus-preserving Gastrectomy (Ppg)mentioning
confidence: 99%
“…As shown in Table 2 , the changes in body weight following PPG and DG were 93.1–97.0% and 90.0–95.0%, respectively. No difference was found between the groups regarding operative time, blood loss, and overall complications [ 55 ].…”
Section: Pylorus-preserving Gastrectomy (Ppg)mentioning
confidence: 99%
“…For patients who have extensive linitis plastica, TG is more frequently performed [26]. Recent reports have indicated that, if R0 can be safely achieved, pylorus-preserving resection for gastric cancer should be considered because no difference in survival was reported compared with more extensive procedures [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…The survival rate of patients with gastric cancer has improved due to early detection and treatment [ 10 , 11 ]. As a result, more patients may develop RGC [ 5 ].…”
Section: Discussionmentioning
confidence: 99%